AB1189-HPR A Telephone Follow-Up after an Integrated Outpatient Osteoarthritis Intervention Does not Enhance Patient Health at 12 Months – Results from A Randomised Controlled Trial. (10th June 2014) - Moe, R.H.; Grotle, M.; Kjeken, I.; Olsen, I.C.; Mowinckel, P.; Haavardsholm, E.A.; Hagen, K.B.; Kvien, T.K.; Uhlig, T.
Abstract : Background: Osteoarthritis (OA) is a frequent chronic musculoskeletal disorder. Patient education is a recommended core treatment, and telephone follow-up has been suggested to improve adherence. Objectives: To examine the effect of a reminder telephone call on health status 4 months after an outpatient visit for patients with hand, hip, knee or generalized OA. Methods: Patients with clinical OA had attended an integrated outpatient OA clinic and half of them an additional 3.5h multidisciplinary group based intervention. After 4 months, all patients were randomized to a 10 minutes telephone follow-up, or no such follow-up. Outcomes included pain, fatigue, and stiffness (NRS, 0-10), Western Ontario and McMaster- (WOMAC) (0-30, 0 is best) and Australian/Canadian (AUSCAN) (0-10, 0 is best) hand- (0-10, 0 is best) osteoarthritis indexes. Group differences were examined by mixed model analyses with random intercept, adjusted for baseline values. Results: Of 390 patients, 86.4% (n=337) were women, and mean age (SD) was 63.1 (8.0) years. There were no significant differences in patient reported health status between the groups at 12 months followup. Conclusions: A single telephone call follow-up at 4 month after a visit to an OA outpatient clinic did not impact patient reported health outcomes at 12 months. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5860